The Presence of Leishmania braziliensis DNA in the Nasal Mucosa of Cutaneous Leishmaniasis Patients and the Search for Possible Clinical and Immunological Patterns of Disease Progression: A Cross Sectional Study - Barroso, Daniel Holanda; Nóbrega, Otávio de Toledo; de Araújo, Carla Nunes; Freire, Gustavo Subtil Magalhães; Martins, Sofia Sales; Rodrigues, Bruna Côrtes; Gomes, Ciro Martins; Sampaio, Raimunda Nonata Ribeiro (Frontiers in Cellular and Infection Microbiology, 2021)
Leishmania braziliensis is the most important causal agent of American tegumentary leishmaniasis (ATL), and 3 to 5% of patients develop mucosal lesions. The mechanisms related to parasite and host immune interactions and the parasite life cycle that lead to dissemination to the mucosa are poorly understood. We aimed to detect L. braziliensis DNA in the nasal mucosa of cutaneous leishmaniasis (CL) patients with early mucous dissemination and to relate those findings to specific inflammatory responses. Nasal swabs were collected from patients with the cutaneous form of ATL. L. braziliensis DNA was investigated using TaqMan-based real-time PCR. The levels of serum cytokines (IL-12, IL-6, TNF-α, IL-10, IL-1β and IL-8) were measured by a multiplex cytometric array. A Poisson regression model was used to test prevalence ratios (PRs) and multivariate interactions of clinical and laboratory characteristics. Of the 79 CL patients, 24 (30%) had L. braziliensis DNA in the nasal mucosa. In the multivariate model, parasite DNA presence in mucosa was associated with a reduction in IL-12 levels (PR = 0.440; p=0.034), increased IL-6 levels (PR = 1.001; p=0.002) and a higher number of affected body segments (PR = 1.65; p<0.001). In this study, we observed a higher rate of early dissemination to the nasal mucosa than what was previously assumed. We suggest that an enhanced Th1 profile characterized by higher IL-12 is important for preventing dissemination of L. braziliensis to the mucosa. Further evaluation of parasite-related interactions with the host immunological response is necessary to elucidate the dissemination mechanisms of Leishmania.